New fears for food irradiation-promise or threat? - Cambridge Educational (Lawrenceville, NJ : Cambridge Educational, 2006., 2006)
The U.S. government has given its stamp of approval to irradiation as a way of killing food-borne bacteria, germs, and parasites. If irradiated food is considered safe enough to give to immune-compromised patients in hospitals and astronauts in space, why is the practice of food irradiation so controversial? This program offers a balanced look at this important method of food purification as it explains how X-rays, electron beams, and gamma radiation are used to sterilize food; identifies watchdog groupsb7(Bthe World Health Organization, the Centers for Disease Control and Prevention, the American Medical Association, and othersb7(Bthat keep an eye on the effectiveness and safety of irradiation technology; and presents the concerns of food irradiation opponents.s
Title from container.
Director and producer, Gayle Friedman.
DVD format.
Keywords: Foodborne diseases; Food Irradiation